Kontribusi Bank Pembiayaan Rakyat Syariah Terhadap Pertumbuhan Ekonomi Provinsi Banten: Analisis Model Pembiayaan UMKM dan Non UMKM - Muhamad Fakhrudin; Ahmad Fatoni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research focuses on the micro scope, namely examining the effect of financing Micro, Small and Medium Enterprises (MSMEs) of Sharia Rural Banks (BPRS) on economic growth in Banten Province. This research has the novelty of comparing MSME and non-MSME financing and the financing model used and its effect on economic growth in Banten Province. This study uses secondary data, namely time series data from 8 BPRS in Banten Province. The data in this study used quarterly data from December 2015 to December 2022. The data was obtained from the financial statements of BPRS Statistics Indonesia (BPS) Banten Province. Meanwhile, the model used in this study is the Error Correction Model (ECM). The results showed that in the long-term model, MSME and Non-MSME financing had a positive and significant effect on the GRDP of Banten Province, but on the contrary, in the short-term model, both variables had a negative influence. Meanwhile, in the short-term model, working capital and investment financing have a positive and significant effect on the GRDP of Banten Province, but in the long-term model, both variables have a negative effect. Simultaneously, financing of MSMEs, Non-MSMEs, working capital, and investment affect the GRDP of Banten Province.